2017
DOI: 10.5194/acp-17-10743-2017
|View full text |Cite
|
Sign up to set email alerts
|

Gasoline aromatics: a critical determinant of urban secondary organic aerosol formation

Abstract: Abstract. Gasoline vehicle exhaust is an important contributor to secondary organic aerosol (SOA) formation in urban atmosphere. Fuel composition has a potentially considerable impact on gasoline SOA production, but the link between fuel components and SOA production is still poorly understood. Here, we present chamber experiments to investigate the impacts of gasoline aromatic content on SOA production through chamber oxidation approach. A significant amplification factor of 3-6 for SOA productions from gasol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 43 publications
9
31
0
Order By: Relevance
“…In addition, photooxidation of vehicular exhaust (dominantly aromatic VOCs) yields abundant precursors for nucleation and growth of UFPs (29,32) as demonstrated in our three different types of measurements. Our ambient and chamber measurements are representative of typical urban environments worldwide (8) since the gasoline fleet of the commonly used vehicle model in China is equivalent to those in Europe and the United States (27). We conclude that NPF under urban environments is mainly driven by organics from local traffic emissions.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In addition, photooxidation of vehicular exhaust (dominantly aromatic VOCs) yields abundant precursors for nucleation and growth of UFPs (29,32) as demonstrated in our three different types of measurements. Our ambient and chamber measurements are representative of typical urban environments worldwide (8) since the gasoline fleet of the commonly used vehicle model in China is equivalent to those in Europe and the United States (27). We conclude that NPF under urban environments is mainly driven by organics from local traffic emissions.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, we evaluated NPF in an enclosed environmental chamber using vehicular exhaust from a gasoline car operating on a chassis dynamometer (SI Appendix, Fig. S2) (27).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…These two unsaturated hydrocarbon species have important effects on air quality (Schell et al, 2001), as decreasing alkene content can decrease fire temperatures and reduce NO x emissions (G. Q. . A new study has also reported that gasoline aromatic hydrocarbons had an essential role in urban SOA production enhancement and thus significantly affected the ambient PM 2.5 (Peng et al, 2017). The limits on aromatic and alkene contents in vehicle gasoline are respectively 40 and 28 % for China IV starting in 2014, 40 and 24 % for China V starting in 2017, and 35 and 18 % for China VI, which is suggested for implementation in 2019 (http://www.nea.gov.cn/).…”
Section: Source Apportionment Using Pmfmentioning
confidence: 99%